2001
DOI: 10.1002/pc.10573
|View full text |Cite
|
Sign up to set email alerts
|

EVOH/clay nanocomposites produced by melt processing

Abstract: Ethylene‐vinyl alcohol copolymer(EVOH)/clay nanocomposites were prepared via a dynamic melt‐intercalation process. The phase morphology and the crystallization behavior of the nanocomposites were investigated, using DSC, DMTA, XRD and SEM. It was found that the treated clay content and dynamic processing time affect the viscosity of the EVOH/clay mixtures: higher clay contents and longer mixing times result in higher torque/viscosity levels. This is due to the increased interaction of the molten polar matrix (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…An increase in melting temperature and melting enthalpy (the melting enthalpy has been normalized for the amount of polymer in the nanocomposites) are also observed in the nanocomposites. This observation is surprising, since some authors have reported crystallinity decreases in EVOH nanocomposites with montmorillonite [6,23,24]. This increase in melting enthalpy is likely to be caused by clay nanoplatelets having a nucleating role on cooling from the melt [25].…”
Section: Properties Of Evoh Nanocompositesmentioning
confidence: 86%
“…An increase in melting temperature and melting enthalpy (the melting enthalpy has been normalized for the amount of polymer in the nanocomposites) are also observed in the nanocomposites. This observation is surprising, since some authors have reported crystallinity decreases in EVOH nanocomposites with montmorillonite [6,23,24]. This increase in melting enthalpy is likely to be caused by clay nanoplatelets having a nucleating role on cooling from the melt [25].…”
Section: Properties Of Evoh Nanocompositesmentioning
confidence: 86%
“…11 In a recent study, it was shown that during melt mixing the processing torque (viscosity) of the EVOH composite with untreated clay (85/15 EVOH/untreated clay) was practically constant, implying that the clay particles remain intact, behaving essentially as regular filler particles. However, the viscosity of the composite with treated clay (85/15 EVOH/treated clay) was rising due to clay fracturing processes, formation of new surfaces, and additional interaction with the EVOH matrix (Fig.…”
Section: Evoh/clay Systemmentioning
confidence: 98%
“…By mixing the organoclay of interest with EVOH, the obtained nanocomposites were shown to provide better mechanical properties than pure EVOH [21][22][23][24][25] . In reality the surfactant is expected to affect the degree of clay dispersion in the polymer matrix, thereby reflecting on the mechanical properties of the nanocomposites.…”
Section: Introductionmentioning
confidence: 97%
“…In the melt-mixing preparation, the organoclay is melt-mixed with the host polymer in an extruder. In fact, the structure and properties of bulk samples of EVOH=clay nanocomposites prepared by the solution precipitation method [25] and melt-mixing method [21][22][23][24] have been investigated. In contrast, this study is focused on the solid-state properties of EVOH=clay nanocomposite films intended for packaging applications.…”
Section: Introductionmentioning
confidence: 99%